MEMAHAMI UNIVERSALITAS ISLAM: PERSPEKTIF DAKWAH MIKRO DAN MAKRO - Achmad Yaman (STAI DI AL-HIKMAH, 2022)
The purpose of this study is to understand the universality of Islam in the macro and micro perspectives of da'wah. This research only uses library research which is part of a qualitative approach. Data analysis by interpreting the existing literature, for example books, journals, books of scholars, and websites that are in accordance with the research theme. The conclusion of the research is that both micro and macro da'wah objectives all lead to one goal. That is changing the way of thinking and the way of life. Both are directed to all areas of human life from the individual to the collective realm. Sometimes in the form of standard formulas, and other times only in the form of moral values and general principles. Everything is based on a comprehensive theory of da'wah and universal characteristics of da'wah